Should all patients with hypertension be worried about developing severe coronavirus disease 2019 (COVID-19)? - Ramin Hosseinzadeh; Mohammad Ali Sheikh Beig Goharrizi; Mansour Bahardoust; Akbar Ghorbani Alvanegh; Mohammad Reza Ataee; Mehdi Bagheri; Ensiyeh Shabani Navidiyan; Seyed Reza Hosseini Zijoud; Mohammad Heiat (BMC, 2021)
Abstract Background Hypertension, the most common comorbidity among coronavirus disease 2019 (COVID-19) patients, is accompanied by worse clinical outcomes, but there is lack of evidence about prognostic factors among COVID-19 patients with hypertension. We have come up with some prognostic factors to predict the severity of COVID-19 among hypertensive patients. In addition, epidemiologic, clinical and laboratory differences among COVID-19 patients with and without underlying hypertension were evaluated. Methods Medical profiles of 598 COVID-19 cases were analyzed. Patients were divided into two comparative groups according to their positive or negative history of hypertension. Then, epidemiologic, clinical, laboratory and radiological features and also clinical outcomes were compared. Results 176 (29.4%) patients had underlying hypertension. Diabetes was significantly higher in hypertensive group [72 (40.9%) vs 76 (18%)] (P-value: 0.001). Cardiovascular and renal disorders were significantly higher in hypertensive patients. (P-value: 0.001 and 0.013 respectively). In COVID-19 patients with hypertension, severe/critical types were significantly higher. [42(23.8%) vs. 41(9.7%)], (P-value: 0.012). In the logistic regression model, Body mass index > 25 (ORAdj: 1.8, 95% CI: 1.2 to 2.42; P-value: 0.027), age over 60 (ORAdj: 1.26, 95% CI: 1.08 to 1.42; P-value: 0.021), increased hospitalization period (ORAdj: 2.1, 95% CI: 1.24 to 2.97; P-value: 0.013), type 2 diabetes (ORAdj: 2.22, 95% CI: 1.15 to 3.31; P-value: 0.001) and chronic kidney disease (ORAdj: 1.83, 95% CI: 1.19 to 2.21; P-value: 0.013) were related with progression of COVID-19. Conclusion Hypertensive patients with Age > 60-year-old, BMI > 25 Kg/m2, CVD, diabetes and chronic kidney disease are associated with poor outcomes in those with COVID-19 infection.